Pengaruh Leader Member Exchange (LMX) dan Budaya Organisasi Terhadap Kinerja Manajerial (Studi Pada Politeknik Negeri Malang) - Andi Asdani (STIE Malangkucecwara, 2019)
Company organizations that aim to remain capable of acting in an increasingly competitive environment for long time, they should also have strong and powerful human resources. Competent human resources are needed in a competitive environment. The purpose of this research is to analyze and explain the influence of leader member exchange (LMX) and organizational culture on managerial performance. The population in this research were employees at the Managerial Level at Malang State Polytechnic. The sampling technique used is the survey method. The results of this research show that LMX variables have a significant effect on managerial employee performance. Organizational culture has a significant influence on organizational performance. And also, the culture variable has a significant influence on managerial performance.